Penggunaan Media Koran Online Untuk Meningkatkan Motivasi Belajar Ekonomi Bagi Siswa Kelas X IPA Di SMA Negeri 1 Ende - Rismayani Ahmad; Sayful Amrin (Program Studi Pendidikan Ekonomi, Universitas Flores, 2018)
This study aims to describe 1) The use of online newspaper media in economics lessons with a scientific approach in class X IPA of SMA Negeri 1 Ende 2) The effect of the use of online newspaper media on economic learning motivation on demand and supply material in class X IPA in SMA Negeri 1 Ende. This type of research is a combination of research with data collection techniques using the Questionnnaire, Obervation and Documentation, the data were analyzed using simple linear regression and product moment correlation. Based on the results of research that the use of online newspaper media as a learning media has an influence on learning motivation, and the use of online newspaper media has an impact on students economic learning motivation.